Whistleblowing System Deployment using ITIL v3 Framework: Evidence from a Public University in Indonesia - Nashrul Hakiem; Luh Kesuma Wardhani; Fajar Nugraha Wahyu; Nenny Anggraini; Imam Marzuki Shofi; Yudi Setiadi (Faculty of Computer Science Universitas Indonesia, 2022)
The Indonesian government has been urged to implement Whistleblowing systems for public services in order to achieve integrity zone development. Almost all service desk software provides user convenience as well as manages the service process in an organisation using standards based on the Information Technology Infrastructure Library (ITIL) v3. The service operation of Whistleblowing systems and the service desk systems are almost the same. However, currently only a few studies have examined the implementation of Whistleblowing systems which uses such a framework in a public higher education institution. The aim of this study is to design and develop a Whistleblowing system which is expected to fulfil the IT Service Management (ITSM) standard and to perform an integration process amongst the community and students. The software was designed and tested in the Universitas Islam Negeri Syarif Hidayatullah Jakarta using the ITIL v3 standards. The result showed that the efficiency parameter value produced a page speed point of 91 % (A). The minimum score was 91 % (A) and the fully loaded time was 2.4 seconds. A portability test showed a value of 100 % for the mobile-friendly score while the reliability test with a stress test also showed at 100 %. The alpha testing result was a very good predicate while beta testing received an acceptable score, good category, and classified as grade C. In conclusion, based on the abovementioned tests, this shows that the system can be used to manage student services, lecturers and staff, as well as to integrate the current service within the community.